The Sensory Properties, Color, Microbial, Lipid Oxidation, and Residual Nitrite of Se’i Marinated with Lime and Roselle Calyces Extracts - G. E. M. Malelak; H. J. D. Lalel; P. R. Kale; I. G. N. Jelantik (Media Peternakan, 2017)
Meat deterioration can occur because of lipid oxidation and bacteria that could affect meat quality. It has been recognized that fruits of lime (Citrus aurantifolia) and roselle (Hibiscus sabdariffa) calyces contain bioactive compounds that have a capability to prevent oxidation and bacterial growth. The objective of this research was to  investigate the effect of lime and roselle calyces extracts on se’i (Rotenese smoked beef) quality. Completely randomized design (CRD) with 2x4 factorial pattern was used in this study. The first factor (E) was source of extracts i.e., lime extract (E1) and roselle extract (E2). The second factor (L) was level of the extract consisted of 4 levels i.e., control (without extract/ L0); L1= 1%; L2= 2%; and L3= 3% (v/v). Each treatment consisted of 3 replications. Sensory properties measured were aroma, taste, and tenderness. Other variables measured were color, total plate count (TPC), thiobarbituric acid reactive substances (TBARS), and residual nitrite.  The taste and tenderness of se’i were affected (P<0.05) by combination of the extract and the level of the extract.  Results showed that there were significant interactions (P<0.05) between the kind of extracts and the level of extract on L (lightness), a (redness), and b (yellowness) values, TPC, TBARS, and residual nitrite values. The level of 3% of  lime extract as well as 3% of roselle calyces extract improved score of taste and tenderness, reduced a values, decreased TPC, TBARS, and residual nitrite values. Marinating in 3% of roselle calyces extract decreased the b value but marinating in 3% of lime increased the b value of se’i. It is concluded that marinating 3% of roselle or 3% of lime gives the best effect on taste, tenderness, TPC, and TBARS values of se’i.